Workbench in the Teaching of Optics to Junior High School - Cuzzamu, Emerson B. (JPAIR Institutional Research, 2018)
Over the last 20 years, not much research has been carried out on improving teaching and learning process of Optics. The new technology in Optics teaching has a lot of advantages, which is impossible to be offered by any book. The study determined the status of textbooks in Physics of Optics in terms of availability, relevance of content, scope of subject-matter, and suitability; the degree of need for workbench in Optics; the validity of the proposed developed workbench in Optics as rated by Physics experts in terms of introduction, learning competencies, presentation of concepts, and exercises. The descriptive-developmental research design was used in the development of the workbench patterned from the ADDIE model. The content of the workbench was based on the competencies present in the K-12 science curriculum guide. The validity of the developed workbench was determined with the use of questionnaires. Results revealed that there is a limited number of textbooks for the subject Physics of Optics and there is an urgent need for a workbench in Optics. The content of the developed workbench is highly valid in terms of introduction, objectives, presentation of concepts and exercises. The developed workbench is strongly acceptable as instructional materials for students of Optics.